Inquiry Learning Strategies in Supporting Economic Learning Activities - Hasyim, Sitti Hajerah; M. Yusuf A. Ngampo; Nurjannah, Nurjannah (International Journal of Education, Vocational and Social Science, 2023)
This study aims to determine the effect of inquiry learning strategies on economic learning activities on accounting material for service company class XII IIS SMA Negeri 3 Takalar. The variables in this study are: (1) Inquiry Learning Strategy as the independent variable, and (2) Learning Activities as the dependent variable. The population in this study were all 139 students in class XII IIS SMA Negeri 3 Takalar, while a sample of 58 students was obtained using the Proportionate Stratified Random Sampling technique. Data collection techniques were carried out by observation, questionnaires and documentation. Data analysis techniques were carried out using descriptive analysis, instrument testing, and hypothesis testing.